Features of Surgical Treatment of Rotary Chest Deformation In Young Children - No'monov Boburmirzo Botirjon o'g'li; Mirzakatimov Bakhromjon Khalimjonovich (Academia One, 2024)
This article analyzes the results of diagnosis and minimally invasive treatment methods of thoracic gyrus deformity in children. Modern examination methods and surgical correction of this disease in children are covered in detail by comparing them
Keywords: chest; thoracoplasty; vortex deformation